Penerapan Prinsip Good Corporate Governance dalam Upaya Penyehatan Keuangan pada AJB Bumiputera 1912 - Haryodharu Putra Santoso; Retno Wulansari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to identify and analyze the implementation of Good Corporate Governance principles in the financial restructuring efforts of AJB Bumiputera and its supervision by the Financial Services Authority (OJK). This research employs a normative legal research method, using case, conceptual, and statutory approaches. The data sources consist of secondary data, including primary, secondary, and tertiary legal materials, and the analysis is conducted through a qualitative method. The findings indicate that the implementation of Good Corporate Governance principles at AJB Bumiputera has not been properly carried out in accordance with applicable regulations. AJB Bumiputera is considered to have failed in fulfilling its obligations to consumers, as evidenced by violations of the right to transparency, unpaid claims or benefits, and the failure to meet financial recovery plan targets As a result, the company is considered to have breached the principles of Good Corporate Governance, leading to the non-fulfillment of policyholders' rights as stipulated in the Insurance Law. The OJK Law stipulates the role of OJK in overseeing the application of Good Corporate Governance principles in insurance companies. The OJK has fulfilled its supervisory responsibilities over AJB Bumiputera by issuing OJK Regulation Number 7 of 2023 concerning Governance and Institutional Arrangements for Mutual Insurance Companies and by imposing administrative sanctions on AJB Bumiputera, including written warnings and partial or full business activity restrictions. Training or outreach programs are required for company management regarding the implementation of Good Corporate Governance principles, strengthening internal audits, the need for a comprehensive supervisory strategy, and the necessity of sanctions that can be imposed on the OJK.